2012
DOI: 10.1007/s00417-012-2003-y
|View full text |Cite
|
Sign up to set email alerts
|

Complication rate and risk factors for intraoperative complications in resident-performed phacoemulsification surgery

Abstract: Residents achieve an acceptable complication rate during their initial 100 phacoemulsification cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 26 publications
7
35
1
Order By: Relevance
“…In our study, the overall intraoperative complication rate (15.12%) was in the upper normal range reported elsewhere (1.8 % to 15%) [5][6][7][8][9][10][11][12] . Th is could be explained by the fact that half of the trainees (4/8) were at the very beginning of the operating learning curve, having only wet lab experience.…”
Section: %supporting
confidence: 64%
See 1 more Smart Citation
“…In our study, the overall intraoperative complication rate (15.12%) was in the upper normal range reported elsewhere (1.8 % to 15%) [5][6][7][8][9][10][11][12] . Th is could be explained by the fact that half of the trainees (4/8) were at the very beginning of the operating learning curve, having only wet lab experience.…”
Section: %supporting
confidence: 64%
“…Unfortunately, even though ophthalmology residents in foreign countries spend a large proportion of their surgical training learning cataract surgery 3 , in our country it was not common practice 4 . As many previous studies showed that complication rates and outcomes of cataract surgery performed by residents were acceptable [5][6][7][8][9][10][11][12] , it was decided to start fi rst resident phacoemulsifi cation-learning program at the Clinical Department of Ophthalmology, Sestre milosrdnice University Hospital Center. Th e purpose of this pilot study was to analyze the resident learning process of phacoemulsifi cation cataract surgery at the Clinical Department of Ophthalmology, Sestre milosrdnice University Hospital Center, and to assess the resident phacoemulsifi cation learning curve in order to implement cataract surgery training into the residency program in the future.…”
Section: Introductionmentioning
confidence: 99%
“…We found that the rate of hospitalization after surgery was significantly higher when operations were performed by residents, perhaps due to a higher prevalence of more severe complications. Although it has been shown that the quality of operations by residents, especially phacoemulsification surgery, is acceptable (29,30), complications such as vitreous loss (31)(32)(33) are more common; therefore, all patients should undergo a complete evaluation before surgery to prevent or reduce the incidence of complications (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…[13] Several other studies showed lower complication rates in residents training programs varying from 3% to 7%. [9][10][11][12][13][14][15][16] …”
Section: P Valuementioning
confidence: 99%
“…Other experienced tutors let residents try the whole procedure all at once. So far a number of teaching techniques have been described [9,10] ; however, to the best of our knowledge there are no published studies in the literature directly comparing their efficacy on resident surgical outcomes.…”
Section: Introductionmentioning
confidence: 99%